Objectives of Industrial Training of Teachers - Gupta, B. L.; Jain, P. C. (Journal of Engineering Education Transformations, 1992)
Majority of Industries complain against the Quality of Polytechnic Passouts especially in respect of conceptual understanding of the subjects and the pratical and supervisory skills they require for working on the shop floor or the field. There is a big gap between what is taught by the teachers in polytechnics and what is practiced in Industries.